Strategies in Rater Training, - Bernardin, H. John; Buckley, M. Ronald (Academy of Management Review, 1981)
There is no evidence to support the belief that training raters to change rating distributions will increase accuracy or validity. Such training may merely promote a temporary and situation-specific response set. We call for a new emphasis in rater training programs on: (1) diary-keeping procedures to increase observational skills; (2) the establishment of a common rater frame of reference to enhance agreement on what constitutes effective job performance; and (3) mastery-based training to increase rater self-efficacy regarding negative appraisal situations.